Contactless devices charger / Arif Adam Mohd Nor & Denis Moris - Mohd Nor, Arif Adam; Moris, Denis (2015)
This Final Year Project is about Contactless Devices Charger. Electronic device is one of the most important things in life. It is considered as a major communication device among people around the world. Most electronic devices have cable(s) connected physically to the device for charging. However, many say that the wires of the charger frequently have problems where the wires are easily damaged. The purpose of this project is to study the technology the concept of transmitting power contactless using inductive method. Inverter is one of the main components in the system where high frequency alternating current (AC) is required. PIC16F877 A will act as a microcontroller which will control the process of the inverter. The transmitted high frequency AC will be converted to DC which may be useful to the load.